“Mendidik dengan Hati dan Keteladanan”: Branding untuk Menumbuhkan Karakter Pendidik Anak Usia Dini - Sri Wahyuni; Ellyn Sugeng Desyanty; Rezka Arina Rahma (Universitas Negeri Medan, 2020)
This study aims to explain the form of character building for early childhood educators through brand